The prognostic value of aspartate beta-hydroxylase in early breast cancer. Issue 3 (September 2022) - Barboro, Paola; Rubagotti, Alessandra; Poddine, Silvia; Grillo, Federica; Mastracci, Luca; Boccardo, Francesco
Purpose: Aspartate beta-hydroxylase (ASPH) is a transmembrane protein involved in cancer progression, which has been shown to imply a worse prognosis in several solid tumors. The aim of the present study was to further investigate the prognostic value of ASPH in early breast cancer. Methods: ASPH expression was investigated through immunohistochemistry in a cohort of 153 breast cancer patients with long-term follow-up, and correlated with clinical–pathological features plus all-cause and breast-cancer-specific mortality. Appropriate statistics were utilized. Results: ASPH negatively correlated with all-cause and breast-cancer-specific mortality. Conclusions: The results of this cohort study support the prognostic value of ASPH in early breast cancer.